Addition of New Exercises and Techniques in the Management of Cervical Pain Syndrome - BASHIR, F (Annals of King Edward Medical University, 2017)
This prospective study was conducted at Physiotherapy department of Lahore General Hospital Lahore and that of Sir Ganga Ram Hospital Lahore, Pakistan on 123 patients from June 1998 to March 2001. Up till now, there are no relaxation exercises defined and not used for the management of cervical pain/syndrome. But this study attempts to describes and emphasize the value and need of application of relaxation exercises in the management of neck pain .Study revealed that these are very effective in terms of early recovery , in reducing number of sick days, in increasing the quality of life and to get long term effects. Therefore, relaxation exercises should be included and applied in the management of neck pain/syndrome.